2019
DOI: 10.3892/mmr.2019.10770
|View full text |Cite
|
Sign up to set email alerts
|

Oxyntomodulin attenuates TNF‑α induced neuropathic pain by inhibiting the activation of the NF‑κB pathway

Abstract: neuropathic pain is rarely diagnosed. oxyntomodulin is peripherally and centrally distributed; however, the potential mechanisms underlying the effects of oxyntomodulin in attenuating nociception remain unclear; thus, we aimed to explore them in the present study. a neuropathic pain model in male c57Bl/6 mice was induced by intrathecal injection of tumor necrosis factor-α (TnF-α), and the duration of nociceptive behavioral responses was measured with a stop-watch timer within 30 min. Western blotting was used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Moreover, its dual agonism GLP1R/GCGR receptors may potentiate these effects ( Pocai, 2014 ). Furthermore, it has been demonstrated that oxyntomodulin is capable of inhibiting the activation of the NF-κB pathway in the spinal cord ( Zhang et al, 2019 ). It is noteworthy that during renal inflammatory processes, immune cells such as neutrophil, monocytes, and macrophages are recruited.…”
Section: Eec Biology and Communication With The Kidneysmentioning
confidence: 99%
“…Moreover, its dual agonism GLP1R/GCGR receptors may potentiate these effects ( Pocai, 2014 ). Furthermore, it has been demonstrated that oxyntomodulin is capable of inhibiting the activation of the NF-κB pathway in the spinal cord ( Zhang et al, 2019 ). It is noteworthy that during renal inflammatory processes, immune cells such as neutrophil, monocytes, and macrophages are recruited.…”
Section: Eec Biology and Communication With The Kidneysmentioning
confidence: 99%